Indirect predictive control techniques for a matrix converter operating at fixed switching frequency - Rivera, Marco; Toleda, Sergio; Tariscotti, Luca; Wheeler, Patrick; Verne, S. (2017)
The direct matrix converter (DMC) has a large number of available switching states, wherewith, the implementa¬tion of predictive control techniques requires high computational resources. In addition, the simultaneous selection of weighting factors for the control of input and output variables of the converter complicates the system tuning. In this paper, two indirect model predictive control strategies are proposed in order to reduce the computational cost and also to avoid the use of weighting factors. The proposal is enhanced with a fixed switching frequency strategy in order to improve the performance of the full system. Results confirm the feasibility of the proposal by demonstrating that it is an alternative to classical predictive control strategies for the direct matrix converter